Acceptability of road pricing and revenue use in the Netherlands - Barry Ubbels; Erik T. Verhoef (European Regional Science Association (ERSA), 2005)
It is generally acknowledged that the implementation of other, more efficient, road pricing measures meet public resistance and that acceptability is nowadays one of the major barriers to successful implementation. Despite the fact that politicians and the public regard transport problems as very urgent and important, people do have concerns about road pricing, resulting in low acceptance levels. This paper presents the empirical results of a questionnaire among Dutch commuters regularly facing congestion asking for their opinion (in terms of acceptance) on road pricing measures and revenue use targets. We find that road pricing is in general not very acceptable and that revenue use is important for the explanation of the level of acceptance. Road pricing is more acceptable when revenues are used to replace existing car taxation or to lower fuel taxes. Moreover, personal characteristics of the respondent have an impact on support levels. Higher educated people, as well as respondents with a higher value of time and with higher perceived effectiveness of the measure, seem to find road pricing measures more acceptable than other people. The same holds for people that receive financial support for their commuting costs and for respondents driving many kilometers in a year. When we ask directly for the acceptability of different types of revenue use (not part of a road pricing measure), again abandoning of existing car (ownership) taxes receives most support whereas the general budget is not acceptable.
Keywords: 330